Study of mechanical and abrasive wear properties of lantana camara particulate reinforced epoxy composite. (2019) - Pradhan, Subhrajit; Rajkonwar, Amit; Kumar Acharya, Samir
Abstract: Natural fibers have gained researchers' attention as a replacement to synthetic materials for reinforcing material in polymers such as epoxy due to their advantages such as environment friendliness, biodegradability, renewability and cost effectiveness. Due to such advantages, further exploration of new natural fibers as a filler material in polymer matrix composites for different tribological applications is needed. Lantana camara is one such abundant natural resources whose potential as filler material in polymer composite has not been explored to such a level till date. The present experimental study aims at studying abrasive wear behavior of lantana camara powder reinforced epoxy composites and their mechanical properties such as tensile and flexural strength. Composites having 10, 20 and 30 wt% of lantana camara powder were fabricated using hand layup technique to study the tensile, flexural, impact strength properties along with abrasive wear behavior on a pin on disc wear tester. It was found that both the abrasive wear resistance and strength of the composite samples can be significantly improved by the incorporation of lantana camara particulates into epoxy. At 20 wt fraction of lantana camara both the wear resistance and strength of the composite were found to be optimum. However, further addition of particulate (30%, 40%) results in increase of wear rate as well as lowering of strength. SEM studies were conducted for the wear out samples to study the failure nature at the microscopic level.